2006
DOI: 10.1016/j.ijfoodmicro.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus parauberis associated with modified atmosphere packaged broiler meat products and air samples from a poultry meat processing plant

Abstract: Lactic acid bacteria (LAB) isolated from marinated or non-marinated, modified atmosphere packaged (MAP) broiler leg products and air samples of a large-scale broiler meat processing plant were identified and analyzed for their phenotypic properties.Previously, these strains had been found to be coccal LAB. However, the use of a 16 and 23S rRNA gene RFLP database had not resulted in species identification because none of the typically meat-associated LAB type strains had clustered together with these strains in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…To confirm the conventional identification of all these 137 isolates and to differentiate between S. uberis and S. parauberis, the 16S and 23S HindIII RFLP patterns (HindIII ribopatterns) of the isolates were analyzed. HindIII restriction enzyme was chosen because it has been found to provide species-specific patterns for various bacteria (Björkroth and Korkeala, 1996;Koort et al, 2005Koort et al, , 2006. Numerical analysis of the patterns, functioning as operational taxonomic units, results in cluster formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm the conventional identification of all these 137 isolates and to differentiate between S. uberis and S. parauberis, the 16S and 23S HindIII RFLP patterns (HindIII ribopatterns) of the isolates were analyzed. HindIII restriction enzyme was chosen because it has been found to provide species-specific patterns for various bacteria (Björkroth and Korkeala, 1996;Koort et al, 2005Koort et al, , 2006. Numerical analysis of the patterns, functioning as operational taxonomic units, results in cluster formation.…”
Section: Resultsmentioning
confidence: 99%
“…The only phenotypic criterion allowing differentiation is the production of β-D-glucuronidase by S. uberis (Khan et al, 2003). During the last few decades, DNA-based methods such as species-specific oligonucleotide probes (Bentley et al, 1993;Harland et al, 1993), PCR-based methods with species-specific primers (Hassan et al, 2001;Alber et al, 2004) or RFLP (Jayarao et al, 1991, McDonald et al, 2005, and 16S and 23S rRNA gene RFLP patterns (ribotypes; Williams and Collins, 1991;Koort et al, 2006) have been used to differentiate between S. uberis and S. parauberis. In addition to the differentiation between S. uberis and S. parauberis, numerical analysis of RFLP patterns, used as operational taxonomic units, has been found reliable for the species level identification in several genera of gram-positive, catalasenegative cocci, when used with validated ribopattern database (Rinkinen et al, 2004;Björkroth et al, 2005;Švec et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus parauberis is an agent of mastitis in cows and thus is a source of economic loss for the dairy industry. Barreiro et al (2010) reported the identification of subclinical cow mastitis pathogens in milk using MALDI-TOF MS. S. parauberis has also been associated with spoilage in meat products (Koort et al, 2006) and has been reported to produce infectious disease in farmed fish, such as turbot (Domenech et al, 1996). Recently, the isolation and MALDI-TOF MS identification of S. parauberis in vacuum-packed seafood products have been reported (Fernández-No et al, 2012).…”
Section: Food Microbial Proteomicsmentioning
confidence: 99%